2022
DOI: 10.3168/jds.2021-21171
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nonpregnant cows and potential embryo losses by color Doppler ultrasound and interferon-stimulated gene expression in grazing dairy cows

Abstract: Many studies have been conducted to estimate pregnancy losses between 19 and 34 d after artificial insemination (AI) in dairy cows managed under confinementbased systems, but few studies have examined embryo mortality during this interval in dairy cows managed under gazing systems. The objectives of this prospective cohort study were (1) to assess the diagnostic value of the corpus luteum (CL) blood perfusion (BP) evaluation by Doppler ultrasound (US) to detect nonpregnant cows at 19 to 20 d post-AI, and (2) t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In addition, a study on cows showed that ET measured by ultrasonography increased when P 4 concentrations decreased (Suguria et al 2018). Similarly, a recent study on cattle evaluating ET to improve the detection of nonpregnant females post-AI showed that ET is thicker in nonpregnant cows because they return to estrus and have lower P 4 concentrations (Madoz et al 2022). Is possible that the in uence of P 4 on ET be different in normal than pathologic endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study on cows showed that ET measured by ultrasonography increased when P 4 concentrations decreased (Suguria et al 2018). Similarly, a recent study on cattle evaluating ET to improve the detection of nonpregnant females post-AI showed that ET is thicker in nonpregnant cows because they return to estrus and have lower P 4 concentrations (Madoz et al 2022). Is possible that the in uence of P 4 on ET be different in normal than pathologic endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Because it is considered a candidate for reliable peripheral detection markers of early pregnancy, it shows promise for the early detection of pregnancy. The ISGs ratio started to rise from 19-20 days in PBLs of pregnant cows in response to IFNT, while it remained unaltered in non-pregnant cows [32]. The ISGs included ISG15, MX1, MX2, and OAS1 mRNA levels were significantly higher in PBL samples from pregnant compared to non-pregnant cows [33].…”
Section: The Pattern Of Stat1 Mrna Expression In Pbls Of Early Pregna...mentioning
confidence: 93%
“…Dos Santos et al (2023) discovered that pregnancy loss in the fixedtime embryo transfer program in cattle was related to luteal blood perfusion. Additionally, using Doppler ultrasound to detect corpus luteum blood perfusion 19-20 days after AI not only diagnoses nonpregnant cows but also assesses pregnancy loss between 19 and 34 days post-AI (Madoz et al, 2022).…”
Section: Cdusmentioning
confidence: 99%
“…Previous studies have shown that IFNT regulates embryo implantation by inducing genetic expression of ISG15 (Johnson et al., 2001), MX1 and MX2 (Austin et al., 2004), OAS1 (Madoz et al., 2022), in turn, activating the Janus kinase and transcriptional activator signalling pathways (Kikuchi et al., 2019). Consequently, ISG15 and MX2 levels of peripheral blood leukocytes can predict non‐pregnant or pregnancy loss in dairy cows (Han et al., 2006; Wijma et al., 2016).…”
Section: Ifnt and Isgsmentioning
confidence: 99%